An Organization Development Intervention to Improve Teacher Innovative Behavior in School of Management - A Case Study of Zhanjiang University of Science and Technology - Liu, Xiaoli; Ruckthum, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
University teachers’ innovative actions significantly contribute to the development of students’ creative abilities and directly impact educational outcomes, research quality, and student growth. This study aims to improve the current state of creative self-efficacy, job autonomy, knowledge sharing, perceived organizational support, and teacher innovative behavior. The study also aims to design and implement practical Organization Development Interventions to foster teacher innovation. It examines the changes in teacher innovative behavior before and after the ODIs, as well as investigates the interconnections among creative self-efficacy, job autonomy, knowledge sharing, perceived organizational support, and teacher innovative behavior. A mixed research method was employed, with 70 full-time teachers from Zhanjiang University of Science and Technology’s School of Management serving as the sample for a four-month intervention. The research utilized both questionnaires and interviews as data collection instruments. The analysis revealed significant differences between Pre-ODI and Post-ODI in both independent variables (creative self-efficacy, job autonomy, knowledge sharing, perceived organizational support) and the dependent variable (teacher innovative behavior). The data analysis results corroborate the existence of positive relationships between creative self-efficacy, job autonomy, knowledge sharing, perceived organizational support, and their influence on fostering teacher innovative behavior. The study revealed the impact of elements such as innovative self-efficacy and job autonomy on the innovative behaviors of university teachers, while also testifying that such behaviors can be effectively enhanced through rationally designed Organizational Development Interventions (ODI). The findings offer valuable insights for research in areas including higher education administration, policy formulation for teacher development, and the optimization of teacher training design.